Policy Reconstruction in Combating Petty Corruption: Towards Progressive, Economic, and Utilitarian Justice - Andhika Prima Sandhy; John Pieris; Aarce Tehupeiory; Hulman Panjaitan (SIGn Jurnal Hukum, 2026)
Combating petty corruption in Indonesia raises normative and budgetary concerns when case-handling costs exceed the losses to state finances or the national economy that can be recovered. This issue must not be understood as a defence of corruption offenders, as corruption remains an extraordinary crime that harms state finances and the social and economic rights of society. The main problem lies in the absence of categorisation of losses to state finances or the national economy under positive law, which results in low-value corruption cases being processed through the formal criminal justice mechanism. This condition is related to Article 4 of Law Number 31 of 1999, which provides that restitution of state financial losses does not extinguish the offender’s criminal punishment. Law Number 1 of 2023 has regulated categories of criminal fines, but it has not established a nominal classification of state losses. This constraint is further reinforced by Article 82 letter c of Law Number 20 of 2025, which excludes corruption crimes from the Restorative Justice mechanism. This study aims to evaluate the urgency of legal reform and construct the Progressive-Economic-Utilitarian Justice Model as a prescriptive recommendation for the legislature. This study employs normative legal research, drawing on conceptual, philosophical, and comparative jurisdictional approaches. The findings show that processing micro-value corruption cases through the formal criminal justice mechanism may result in cumulative losses for the state, namely losses from the criminal offence and additional costs arising from disproportionate law enforcement. As a prescriptive solution, the Progressive-Economic-Utilitarian Justice Model requires limited reform of sentencing norms, a legal basis for the limited application of Restorative Justice, and the legalisation of a maximum state-loss threshold of IDR 50 million as the law as it ought to be (ius constituendum). This mechanism must be subject to restitution of at least 200% of the losses to state finances or the national economy caused by the offence to prevent impunity. Accordingly, the Progressive-Economic-Utilitarian Justice Model is directed as a strict loss-recovery mechanism to protect state finances and the social and economic rights of society.